Discounted Cash Flows, Price Level Adjustments and Expectations: A Comment. - Greer, Willis R. (The Accounting Review, 1972)
Abstract The article is a comment on an article "Discounted Cash Flows, Price Level Adjustments and Expectations," by researcher, Harold Bierman Jr., published in the October 1971 issue of the journal "The Accounting Review." Bierman suggests that the book value of his $1,529 asset would be shown as $1,036 on a price-level adjusted position statement which is "too high a value since the present value of the asset is $901." This "finding" leads to his major conclusion. According to the author, such a statement is not consistent with the manner in which price-level adjustments are and should be made. In fact, price-level adjustments are simply translations from one unit of currency to another. The projection of cash flows is correct but it must be noted that this schedule is expressed in monetary amounts reflecting the change in price level between periods. A schedule can, and should, be re-cast into three separate schedules, each using a uniform value of currency. A correct statement of economic depreciation for the first period, has been provided.